Cyprus : Second Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria. - International Monetary Fund. European Dept. (Washington, D.C. : International Monetary Fund, 2013)
This paper discusses Cyprus' Second Review Under the Extended Arrangement Under the Extended Fund Facility and Request for Modification of Performance Criteria. The program is on track. Fiscal performance continued to exceed targets comfortably, and the 2014 budget is more ambitious than envisaged at program approval. All structural benchmarks were met, albeit with a modest delay in one case. Significant progress has been made in restructuring and recapitalizing the banking sector, including with foreign participation in the share capital of one domestic bank. Fiscal structural reforms are proceeding, but strong resolve is needed to kick start the privatization process.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet